(untitled) (Journal of Comparative Social Work, 2025)
In Uganda, the social work profession was introduced by the British colonial government, and therefore activated as a tool of colonial state control. Consequently, the profession adopted Western philosophies with a disregard for indigenous social support philosophies. It used a non-political stance to counter political dissent, resistance and activism against the colonial administration. In the decades that have followed, the profession’s invisibility in politics and activism has undermined its critical contribution to challenging injustice in social policy and society. In this article, we challenge this apolitical epistemology of social work in Uganda rooted in the profession’s colonial past, the country’s violent political history and contemporary neoliberal economic choices. We use a case analysis of the political contestations, human rights violations and human victims in the 2021 presidential elections in Uganda. We conducted a thematic analysis of data sourced from both print and electronic media, election observer reports and human rights reports. From this analysis, we argue that Uganda’s political contestations produce widespread state- and non-state-driven human rights violations. We articulate that the resultant countless human victims can no longer be ignored, and should compel social work as a profession that seeks to promote social justice into action. From a decolonial standpoint, we stress that social work’s continued inaction cannot safeguard the profession’s social justice mission amidst Uganda’s political contestations. Since the outcomes of these political contestations profoundly impact social justice, human rights and the well-being of the majority of the communities, we argue that the social work profession in Uganda must galvanise the commitment to engage in the politics of the day vigorously and publicly. We conclude by making calls for social work actions that utilise indigenous pathways in building a credible political leadership that safeguards the rights and wellness of society.